Understanding the Sights, Sounds, Feelings, Taste and Smells of Commercial Air Travel - Smith, Andrew T. (My University, 2010)
This paper and presentation will provide knowledge about general and technical aspects of flight and air travel including security, ground operations, flight operations, airline personnel training, responsibilities and more.
Keywords: Commercial air travel; Aviation industry